Intellectual Capital and Firm Performance: Empirical Evidence from the Jakarta Islamic Index - Prasojo Prasojo; Sofyan Hadinata (Journal of Accounting Auditing and Business, 2020)
Measurement of intellectual capital is fundamentally crucial for companies. It enables managers to allocate economic resources to improve knowledge assets in order to support a sustainable competitive advantage for the companies.This study presents a method of residual income model (RIM) to measure intellectual capital (IC). This method quantitatively assesses intellectual capital using knowledge-based view perspective. Purpose of the study is to examine the relationship of intellectual capital with company financial performance empirically. This study uses panel data regression with research objects listed in the Jakarta Islamic Index from 2014to 2017. The results of this study indicate that intellectual capital does not affect the company's financial performance